Semiarid grasslands and extreme precipitation events: do experimental results scale to the landscape? - Alison K. Post; Kristin P. Davis; Jillian LaRoe; David L. Hoover; Alan K. Knapp (Ecology, 2021)
The frequency and magnitude of deluges (extremely large rain events) are increasing globally as the atmosphere warms. Small‐scale experiments suggest that semiarid grasslands are particularly sensitive to both the timing and size of deluge events. However, the assumption that plot‐scale results can be extrapolated across landscapes with variable soil textures, plant communities, and grazing regimes has seldom been tested, despite being key to forecasting regional consequences of precipitation extremes. We used precipitation data from an extensive rain gauge network to identify natural deluges (mean size = 60 ± 31 mm, 1984–2012) that occurred across a ˜60‐km 2 heterogeneous native shortgrass steppe landscape in Colorado. We then related spatial variation in deluge precipitation to postdeluge responses in canopy greenness (normalized difference vegetation index, NDVI) via satellite imagery. Consistent with results from experiments, this semiarid grassland was most sensitive to mid–growing‐season deluges, and postdeluge canopy greenness usually increased linearly (67% of the time) with increasing deluge size. This suggests that aboveground productivity in these semiarid systems will likely increase, rather than asymptote, with forecasted increases in deluge size. Importantly, differences in grazing regime did not significantly alter deluge responses, indicating that these patterns are robust to this widespread management practice.